PENGARUH HARGA, KELENGKAPAN PRODUK DAN DISPLAY PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Bandung Super Model Cabang Dinoyo Kota Malang) - Yunia Lindawati; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this study is to determine the effect of price, completeness of products and product displays of purchasing decisions on consumers super model Bandung branch Dinoyo Malang. This research is Quantitative research. Population in this research is all consumer of Bandung Super Model of Dinoyo branch of Malang city. The sampling technique used purposive sampling technique, while the data analysis method used in this research is multiple linear regression analysis. The results of this study provide empirical evidence that the variable Price, Product Fittings and Display Products both simultaneously and partially have a positive and significant impact on purchasing decisions.Keywords: price, product completeness, product display and purchase decision.